Springback analysis of L-sectioned bar of linear work-hardening materials under torsional loading - Lal R.K.; Dwivedi J.P.; Singh V.P.; Choubey V.K.; Srivastava S.K. (My University, 2025)
This paper deals with the torsional springback problems of L-sectioned bars of linear work-hardening materials. Using the deformation theory of plasticity, a numerical scheme based on the finite difference approximation has been proposed. The growth of the elastic-plastic boundary and the resulting stresses while loading, and the torsional springback and the residual stresses after unloading are calculated. The results are verified experimentally with mild steel bars having a L cross-section and the experimental result have been found to agree well with the theoretical results obtained numerically. © 2017 Inderscience Enterprises Ltd.